Scoring rules for judgment aggregation - Dietrich, Franz (Social choice and welfare, 2014)
This paper introduces a new class of judgment aggregation rules, to be called 'scoring rules' after their famous counterparts in preference aggregation theory. A scoring rule generates the collective judgment set which reaches the highest total 'score' across the individuals, subject to the judgment set having to be rational. Depending on how we define 'scores', we obtain several (old and new) solutions to the judgment aggregation problem, such as distance-based aggregation, premise- and conclusion-based aggregation, truth-tracking rules, and a generalization of the Borda rule to judgment aggregation theory. Scoring rules are shown to generalize the classical scoring rules of preference aggregation theory.